Nie-poetyka, czyli w stronę paratopiczności - Zaleski, Marek (Poznańskie Studia Polonistyczne. Seria Literacka, 2017)
Poetics proposed by structuralists at its best did not respect its own premises in a dogmatic manner. It profited knowledge that today’s Theory (or so-called Post-Theory) considers helpful while dealing with the text. Unlike approaches held on metodologically narrow perspective, the heterogenic Post-Theory has a capacity for the reneval because it pays due regard to the consideration of paratopia of literaty text. It often happens that post-Theory is accused of obscurity and hermeticism, but „ignotum per ignotum, obscurum per obscurum rhetorics” is not always a vice, sometimes it seeks to respect the mystery of the text and its secret language.